Table Tennis Player Agility : Hexagon Drill on Sand or Ladder Drill - Gussanto, Amin Brilian Wicaksono (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi FKIP Universitas PGRI Mahadewa Indonesia bekerjasama dengan Asosiasi Prodi Olahraga Perguruan Tinggi PGRI (APOPI), 2025)
Agility is one of the crucial physical abilities for a table tennis athlete. In a match, the ability to move quickly and responsively often determines success. In addition to endurance and strength, agility plays a vital role as one of the primary attributes that differentiate regular athletes from elite ones. This study focuses on analyzing the impact of two training methods, namely the hexagon drill in a sandpit and the ladder drill, on improving the agility of table tennis players. The subjects of the study included students participating in the extracurricular table tennis activities at MIN 1 Kota Madiun. This approach was designed to evaluate the effectiveness of each method in enhancing agility, which is a key aspect of table tennis performance. A quasi-experimental method with a One Group Pretest-Posttest Design was employed in this research, involving agility measurements before and after the treatments were applied. The results of the study indicated that while both training methods positively impacted the players' agility, the ladder drill produced a more significant improvement compared to the hexagon drill in the sandpit. These findings provide valuable insights into the effectiveness of training methods in enhancing the agility of table tennis athletes.